Jūrmala City Public Transport Compliance with the Universal Design Principles - Vīksniņa, Ina; Vītoliņa, Kristīne; Priede, Līga; Ozola, Ina; Erkena, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Integration of humans into society as the full members of it is to take active part in social activities, but not for all people it is possible due to physical barriers that limit integration. People, who are facing different environment related obstacles - integration problems, are people with disabilities, elderly, mothers with small children and prams. Successful integration is based on adapted environment that is based on principles of the universal design. Public transport is an important resource of integration, therefore it is important to ascertain its availability. In order to ascertain the views of the universal design principles about providing public transport services, the study has been carried out. The aim of the study was to examine implementation of the universal design principles in accessibility of public transport services.